Implementasi Green Economy di Indonesia Perspektif Maqashid Syariah - Sari, Eka Puspita; Isman, Ainul Fatha (Journal of Islamic Economic Studies, 2025)
Green economy comes as a form of prevention of environmental problems affected by economic activity in various sectors. The purpose of this research is to analyze the concept of green economy and its relevance to maqashid sharia principles and its implementation in Indonesia. The research method used is qualitative descriptive analysis with a literature study approach. The results showed that the concept of green economy is in line with the principles of maqashid sharia to achieve the benefit and welfare of society. The concept of green economy has existed in Indonesia since 1972 and began to get attention by some elements of society in 1992. The implementation of the green economy in Indonesia in Asia Pacific countries with an environmental sustainability score of 28.2. Green Economy needs to be developed such as Green Investment, Green Banking and greening education as well as mature regulations from various parties so that the realization of the green economy transition can be realized properly.